Planetary radar science case for EISCAT 3D - Tveito, Torbjørn; Vierinen, Juha; Gustavsson, Björn Johan; Narayanan, Viswanathan Lakshmi (Annales Geophysicae, 2021)
Ground-based inverse synthetic aperture radar is a tool that can provide insights into the early history and formative processes of planetary bodies in the inner solar system. This information is gathered by measuring the scattering matrix of the target body, providing composite information about the physical structure and chemical makeup of its surface and subsurface down to the penetration depth of the radio wave. This work describes the technical capabilities of the upcoming 233 MHz European Incoherent Scatter Scientific Association (EISCAT) 3D radar facility for measuring planetary surfaces. Estimates of the achievable signal-to-noise ratios for terrestrial target bodies are provided. While Venus and Mars can possibly be detected, only the Moon is found to have sufficient signal-to-noise ratio to allow high-resolution mapping to be performed. The performance of the EISCAT 3D antenna layout is evaluated for interferometric range–Doppler disambiguation, and it is found to be well suited for this task, providing up to 20 dB of separation between Doppler northern and southern hemispheres in our case study. The low frequency used by EISCAT 3D is more affected by the ionosphere than higherfrequency radars. The magnitude of the Doppler broadening due to ionospheric propagation effects associated with traveling ionospheric disturbances has been estimated. The effect is found to be significant but not severe enough to prevent high-resolution imaging. A survey of lunar observing opportunities between 2022 and 2040 is evaluated by investigating the path of the sub-radar point when the Moon is above the local radar horizon. During this time, a good variety of look directions and Doppler equator directions are found, with observations opportunities available for approximately 10 d every lunar month. EISCAT 3D will be able to provide new, high-quality polarimetric scattering maps of the nearside of the Moon with the previously unused wavelength of 1.3 m, which provides a good compromise between radio wave penetration ...